The Rise of the Dutch Republic $1 (BVolume 04: 1555-59s - Motley, John Lothrop, 1814-1877 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Rise of the Dutch Republic $1 (BVolume 04: 1555-59" by John Lothrop Motley is a historical account written in the mid-19th century. The work delves into the political and military events during a pivotal time in the history of the Netherlands, particularly focusing on the reign of Philip II of Spain and the ensuing struggles for power and autonomy in the region. The volume covers key figures such as Philip II, Count Egmont, and the Duke of Alva, examining their roles during a period marked by religious tensions and military conflicts. At the start of this volume, the narrative introduces Philip II's ascension to power in the Netherlands and presents a detailed portrait of his character and governance style. The text describes his marriage to Mary Tudor and the implications of his rule, particularly how his foreign background and inclination toward oppressive policies created friction with the local populations. The opening chapters explore the political machinations and rivalries within his court, notably between Ruy Gomez, a favorite of Philip, and the Duke of Alva, setting the stage for the broader conflicts that would ensue in the region, including decisive battles, military campaigns, and the brewing animosity between the Spanish crown and the Dutch provinces. (This is an automatically generated summary.)s
Release date is 2004-01-01
This etext was produced by David Widger
Keywords: Netherlands -- History -- Eighty Years' War, 1568-1648; Netherlands -- Church history